Quorum sensing and QsvR tightly control the transcription of vpa0607 encoding an active RNase II-type protein in Vibrio parahaemolyticus - Zhang, Yiquan; Xue, Xingfan; Sun, Fengjun; Li, Xue; Zhang, Miaomiao; Wu, Qimin; Zhang, Tingting; Luo, Xi; Lu, Renfei (Frontiers in Microbiology, 2023)
Vibrio parahaemolyticus, a Gram-negative, halophilic bacterium, is the leading cause of acute gastroenteritis in humans. AphA and OpaR are the master quorum sensing (QS) regulators operating at low cell density (LCD) and high cell density (HCD), respectively. QsvR is an AraC-type protein that integrates into the QS system to control gene expression by directly controlling the transcription of aphA and opaR. However, the regulation of QsvR itself remains unclear to date. In this study, we demonstrated that vpa0607 and qsvR were transcribed as an operon, vpa0607-qsvR. AphA indirectly activated the transcription of vpa0607 at LCD, whereas OpaR and QsvR directly repressed vpa0607 transcription at HCD, leading to the highest expression levels of vpa0607 occurred at LCD. Moreover, VPA0607 acted as an active RNase II-type protein in V. parahaemolyticus and feedback inhibited the expression of QsvR at the post-transcriptional level. Taken together, this work deepens our understanding of the regulation of QsvR and enriches the integration mechanisms of QsvR with the QS system in V. parahaemolyticus.